A genetic approach towards optimal color image quantization - Scheunders, P. (1996 IEEE International Conference on Image Processing Proceedings, 1996)
In this paper the problem of local optimality of color image quantization procedures is discussed. The well-known and frequently used C-means clustering algorithm (CMA) is applied to the problem, and its dependence on initial conditions is studied. A hybrid approach, combining CMA with a genetic algorithm is constructed, and it is shown that this approach is insensitive to its initial conditions. Results compare the performance of the genetic approach with CMA on three different types of initial conditions: random initial conditions and two popular color image quantization algorithms: the median-cut algorithm and the variance-based algorithm. In all cases the genetic approach outperforms CMA.